Sosialisasi Pemberdayaan Perempuan Melalui Urban farming di Desa Senggigi - Dewi, Suprayanti Martia; Maryanti, Sri; Cecilia, Sisca; Kisman, Kisman; Putri, Dwi Noorma; Jihadi, Amrul (Jurnal Gema Ngabdi, 2025)
The urban farming outreach and mentoring program in Senggigi Village aims to empower women, particularly members of the local TP-PKK group, in strengthening household food security by utilizing limited home garden space. The method used involved participatory approaches, including formal and informal socialization, sustainable farming training, and implementation of Integrated Farming Systems such as vertical gardening and catfish cultivation in buckets. The results indicate a 100% increase in partner knowledge on urban farming fundamentals. This activity hopefully will contribute to the productivity of home gardens and increases awareness of the importance of household-based food security.